A Review – The Influence of Games on Education Development in the Disruption Era - Anugerah Bagus Wijaya; Toni Anwar (Universitas Amikom Purwokerto, 2023)
Game is a platform that is commonly used by users in everyday life. Games are often used when someone is bored, bored, and mostly as a means of entertainment. But in the current era of disruption in technology, games are also used as learning media. Game-based learning is a learning concept that uses games as a tool to increase student involvement and motivation in learning. In game-based learning, games designed with learning objectives are called serious games. Serious games combine elements of fun and engaging games with learning objectives to create interactive, effective, and engaging learning experiences for students. In serious games, students play games that have learning objectives, such as learning new skills, understanding complex concepts, or honing certain skills. Currently known as gamification in learning. This paper will review several issues related to games in learning. The method used in finding several gap issues related to the author uses bibliometric techniques which are processed using bibliometric analysis. The author uses archival data from Scopus sources which review game technology in learning. The facts resulting from the analysis consist of 4 elements of discussion namely, technology, media, materials, methods, and the latest findings on the data security side. This author obtains data related to the security side, namely in the user privacy section. This means that the discussion that will take place later will be the theme of games that discuss elements of data security.